2012
DOI: 10.1002/yea.2937
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Candida in the oral cavity and its differentiation based on the internally transcribed spacer (ITS) regions of rDNA

Abstract: This study aimed to determine the distribution of Candida species in the oral cavity and differentiate the species based on PCR amplification, including HinfI and MspI digestion, in order to assess the effectiveness of using the rDNA region for species identification. Samples from saliva as well as palate, tongue and cheek mucosa surfaces were collected from 45 individuals, consisting of three groups: periodontal disease patients; denture-wearers; and the control group. The samples were serially diluted, sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Although the percentages of subjects with yeasts across the duration of the clinical trial were similar to the previous study conducted by Lam et al, the levels of yeasts were much lower (Lam et al, ). The levels of yeasts documented in the present study are more comparable to a study carried out among healthy subjects—which reported viable counts of yeasts of ~2.0 × 10 3 cfu/ml from tongue, palate, buccal mucosa samples (Zahir & Himratul‐Aznita, ).…”
Section: Discussionsupporting
confidence: 87%
“…Although the percentages of subjects with yeasts across the duration of the clinical trial were similar to the previous study conducted by Lam et al, the levels of yeasts were much lower (Lam et al, ). The levels of yeasts documented in the present study are more comparable to a study carried out among healthy subjects—which reported viable counts of yeasts of ~2.0 × 10 3 cfu/ml from tongue, palate, buccal mucosa samples (Zahir & Himratul‐Aznita, ).…”
Section: Discussionsupporting
confidence: 87%
“…They found that the candidal loads of the saliva, tongue, palate, and buccal mucosa of denture-wearers were significantly higher than those of the control group [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The PCR amplification of the ITS1-5.8S-ITS2 region in ribosomal DNA was carried out by forward (5’-TCCGTAGGTGAACCTGCGG-3’) and reverse (5’TCCTCCGCTTATTGATATGC-3’) primers [24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral Candida species are usually harmless, but they may become pathogenic under immunosuppressive conditions, with the presence of dentures, or with impaired salivary flow. Candida species of clinical interest include: C. albicans, C. tropicalis, C. krusei, C. parapsilosis, C. dubliniensis, C. glabrata, and C. lusitaniae [5].…”
Section: Introductionmentioning
confidence: 99%